Induction of Oxidative Stress in Kidney - Emin Ozbek (International Journal of Nephrology)
Oxidative stress has a critical role in the pathophysiology of several kidney diseases, and many complications of these diseases are mediated by oxidative stress, oxidative stress-related mediators, and inflammation. Several systemic diseases such as hypertension, diabetes mellitus, and hypercholesterolemia; infection; antibiotics, chemotherapeutics, and radiocontrast agents; and environmental toxins, occupational chemicals, radiation, smoking, as well as alcohol consumption induce oxidative stress in kidney. We searched the literature using PubMed, MEDLINE, and Google scholar with “oxidative stress, reactive oxygen species, oxygen free radicals, kidney, renal injury, nephropathy, nephrotoxicity, and induction”. The literature search included only articles written in English language. Letters or case reports were excluded. Scientific relevance, for clinical studies target populations, and study design, for basic science studies full coverage of main topics, are eligibility criteria for articles used in this paper.